Mechanical design for collaborative robot (CoBot) platform and autonomous mobile robot (AMR) - coupling and decoupling (I) - Pan, Yimou (Nanyang Technological University, 2023)
Collaborative robots (Cobot) are advanced robots that are designed for human-machine interaction in close proximity. Cobot differs from traditional industrial robots which works in independently with minimum human contact involved. This new technology has emerged to help human with various tasks, and it has gotten more popular as development advances in recent years, making automation easier than ever.